Melting Characteristics of Milk Chocolate with Different Sweetener Blends - Zaizuliana Rois Anwar, Nurul; Afifa Hashim, Nur; Asyikeen Zulkifli, Noroul (International Journal of Engineering and Technology, 2018)
Chocolate is a cocoa based product derived from cocoa beans the seed of Theobroma cocoa tree. Nowadays, the demand of natural sweetener for manufacturing of sugar-free chocolate has dramatically increased. However, their applicability in product formulation and how it affects the quality of chocolate still remain a big challenge. Despite providing sweet taste in chocolate, bioactive compounds present in stevia leaves, palm sugar and honey could enhance human health. The effects of Stevia leaves powder, palm sugar and honey on the melting characteristic and crystallization of the milk chocolate were measured using differential scanning calorimeter (DSC). The melting peak of all those sweeteners are in the range of 37-38 ℃ indicating the presence of form VI polymorphs. However, the presence of multiple peaks was also observed showing that there was a competition between the growth of low and high stability polymorphs. Besides, only the substitution of sugar with honey produced a significant change in the enthalpy value (p<0.05). From the results obtained, it can be concluded that stevia leaves powder, palm sugar and honey could be used for sugar free chocolate.